Development and psychometric properties of the conscience-based nursing care scale - Khoddam, Homeira; Ebadi, Abbas; Modanloo, Mahnaz; Kalantari, Soheyla (Frontiers in Psychology, 2025)
BackgroundIt is clear that nurses’ conscience plays an important role in guiding professional decision-making and ensuring quality patient care. Additionally, it positively impacts nursing performance and promotes ethical care in clinical settings.AimsThis study aimed to develop and validate the conscience-based nursing care scale (CNS) based on the clinical nurse care setting in Iran.MethodsThis study is a sequential exploratory mixed-methods study. The concept of “conscience-based care” was clarified using Schwartz-Barcott and Kim’s hybrid concept analysis method, which included a comprehensive literature review and qualitative fieldwork involving in-depth interviews with five nurses. Then, the psychometric properties of a newly developed scale, based on the themes identified in the first phase, were evaluated. This included item generation, face and content validity assessments, a pilot study, and both exploratory and confirmatory factor analyses.ResultsThe developed scale has 24 items spread across five factors, namely accountability in conscientious care, responsibilities in care, attention to the quality of care and teamwork, importance to the reputation and dignity of the profession, and ethics in care. For each item, five options (always, most of the time, sometimes, rarely, and never) were considered, with the numerical value of each being always = 5, most of the time = 4, sometimes = 3, rarely = 2, and never = 1 determined based on the meaning of the item. Exploratory and confirmatory factor analyses confirmed its structure, explaining 43.79% of the variance in conscience-based care. The scale demonstrated high reliability (ICC = 0.959) and responsiveness to change, with minimal ceiling and floor effects.ConclusionThis study validated the CNS in an Iranian clinical setting, demonstrating its reliability and validity. Nursing managers and policymakers can confidently use this scale to assess the quality of nursing care and encourage nurses to provide conscience-based care.